The Effect of Addition Pineapple Peel Meal (Ananas comosus (L) Merr) in Diet on Total Egg and Egg Duck Quality - Muharlien Muharlien; Vitra Vitra; Muhammad Halim Natsir (Faculty of Animal Science Universitas Brawijaya, 2011)
The aim of this research was to study the effect of addition pinneapple peel meal in diet on total egg and egg quality duck. Materials of the research were 60 mojosari ducks at seven months old. The treatment of pineapple peel meal addition in diet were treatment on level of 0, 2, 4, 6 and 8%. Variable were numbers of egg, egg shell thickness, fat and cholesterol egg yolk. The datas were analyzed using ANOVA from Randomized Block Design (RBD), if the result had significant effect, would be continued by Duncan’s Multiple Range Test (DMRT). The result showed that an addition pineapple peel meal in duck diet had no effect (P>0,05) on numbers of egg and thick of egg shell, however, it had highly significant effect (P<0,01) on fat and cholesterol egg yolk . The concluded showed that the addition of pineaple peel meal in ducks diet can be decreasing fat and cholesterol egg yolk and can not decreasing numbers of egg and egg shell tick. Keywords: Mojosari ducks, total egg, egg shell thick, egg yolk fat, and egg yolk cholesterol